Climate change and sustainable cities - Priemus, Hugo, 1942-; Davoudi, Simin (London : Routledge, 2014)
Climate change has demonstrated the complexities of the human-nature interrelationship and the need for embedding an environmental consciousness into our social values and norms. This book explores this interaction and urges planners to revisit some of their concepts, methods and ways of thinking.
Originally published in European planning studies, volume 20, issue 1 (January 2012) and issue 3 (March 2012).
Includes bibliographical references and index.
Keywords: Sustainable urban development; City planning -- Environmental aspects; Climatic changes